2017
DOI: 10.1186/s12885-016-2978-6
|View full text |Cite
|
Sign up to set email alerts
|

Which symptoms are linked to a delayed presentation among melanoma patients? A retrospective study

Abstract: BackgroundThe incidence of melanoma is rising. Early detection is associated with a more favourable outcome. The factors that influence the timing of a patient’s presentation for medical assessment are not fully understood.The aims of the study were to measure the nature and duration of melanoma symptoms in a group of patients diagnosed with melanoma within the preceding 18 months and to identify the symptoms and barriers associated with a delay in presentation.MethodsA questionnaire was distributed to a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(49 citation statements)
references
References 20 publications
0
49
0
Order By: Relevance
“…1494 were females (mean: 249, median: 74.5) and 874 males (mean: 124.86, median: 49). Four studies collated ethnicity 16,26–28 of these, participants were white or Caucasian, which is consistent with typical epidemiology of melanoma 29 . Only one study provided skin type data 27 .…”
Section: Resultsmentioning
confidence: 77%
“…1494 were females (mean: 249, median: 74.5) and 874 males (mean: 124.86, median: 49). Four studies collated ethnicity 16,26–28 of these, participants were white or Caucasian, which is consistent with typical epidemiology of melanoma 29 . Only one study provided skin type data 27 .…”
Section: Resultsmentioning
confidence: 77%
“…It was reported that white ethnicity was a risk factor of survival, which reflects that the melanoma occurred more frequently in people with paler skin. 36 This may be caused by fair-skinned individuals having the highest risk of sunburn and skin cancer. In the present analysis, other ethnicities had the longest OS, whereas the white group had the shortest OS.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 112 melanoma patients in this study, 67 (59.8%) experienced a delay in presentation (DSMA longer than three months [ 7 ]), and the DSMA of these 67 patients ranged from 4 months to 361 months. The longer the DSMA, the longer the progression of the disease and the delay in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma has a poor prognosis. In western studies, the 5-year survival rate of different stages of melanoma decreased from 91.4% (stage I) to 24.6% (stage IV), and non-ulcerative and Breslow thickness <1 mm melanoma have the best prognosis [ 7 , 8 ]. In China, the melanoma patients’ 5-year survival rate and median survival time were 41.6% and 43 months, and the 5-year disease-free survival (DFS) rate and median DFS time were 12.3% and 20 months, respectively [ 9 ].…”
Section: Introductionmentioning
confidence: 99%